Peningkatan Hasil Belajar IPS Materi Pejuang Pada Masa Penjajahan Belanda Dan Jepang Melalui Tipe Jigsaw - Okta Rosfiani; M. Ashar; Faizhikam Arham; Yanti Oktaviani; Muhammad Fachri; Tanjung Essa (Journal on Education, 2025)
This research aims to examine the effectiveness of implementing the jigsaw-type cooperative learning model in improving student learning outcomes in material on the struggles of warrior figures during the Dutch and Japanese colonial periods in social studies classes in elementary schools. The jigsaw model, which emphasizes collaboration between students and active learning, is used to overcome difficulties experienced or faced by students in understanding historical material. This research was carried out in class V of An Nuriyah Jagakarsa Islamic Elementary School using the classroom action research (PTK) method, which is based on a cycle of planning, action, observation, and reflection. The research results showed a significant increase in student learning outcomes, measured through tests and observation of student participation, which was affected by the rise in the percentage of complete learning outcomes from 31.42% in the pre-cycle to 94.28% in the second cycle. Applying the jigsaw model also increases student motivation and involvement in history learning. This research concluded that the jigsaw model was effective in increasing students' understanding of the struggle material of warrior figures and could also improve the quality of social studies teaching in elementary schools.